Transitional Territories : Confluence of Art and Anthropology in the Practices of Contemporary Artists from Turkey - Güngör, Ayşe (Image (Transcript (Firm)) ;, 2022)
Ayse Güngör investigates art practices between art and anthropology in Turkey, as well as the implications of contemporary art for those disciplines. She discusses various approaches based on anthropological theories on the forms of relation and theories of artistic practices on socio-political issues. Based on long-term research with contemporary artists such as Nil Yalter, Gülsün Karamustafa, Esra Ersen, Kutlug Ataman, Tayfun Serttas, Köken Ergun, Dilek Winchester and Artikisler Collective, this book analyzes the objectives of art and anthropology in order to determine new possibilities and divergences arising from this interdisciplinary confluence.